2021
DOI: 10.19087/jveteriner.2021.22.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Penggunaan Antibiotik yang Kurang Tepat pada Peternakan Babi di Kota Kupang, Nusa Tenggara Timur

Abstract: Misuse of antibiotics has the potential to accelerate the emergence of types that are resistant to inappropriate drugs. This study aims to evaluate the inappropriate use of antibiotics in pig farms in the City of Kupang, East Nusa Tenggara. This antibiotic use evaluation study was conducted from March to May 2018. This study was conducted on 100 pig farmers spread across 6 (six) districts in Kupang City. The sampling technique was done by stratified random sampling method based on the characteristics or types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…According to Jurnalis et al [3], tetracycline is the most common antibiotic class available in public healthcare centers. Kallau et al [4] and Detha et al [5] reported that tetracycline is the common antibiotic used to treat pigs in Indonesia. Some studies have shown that bacterial species resist tetracycline through their tet genes [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Jurnalis et al [3], tetracycline is the most common antibiotic class available in public healthcare centers. Kallau et al [4] and Detha et al [5] reported that tetracycline is the common antibiotic used to treat pigs in Indonesia. Some studies have shown that bacterial species resist tetracycline through their tet genes [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] and Detha et al . [ 5 ] reported that tetracycline is the common antibiotic used to treat pigs in Indonesia. Some studies have shown that bacterial species resist tetracycline through their tet genes [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tetracyclines are commonly used in humans and livestock due to their broad-spectrum activity, availability, and affordability. These antibiotics are mostly available in healthcare units, especially community health centers (Puskesmas) [8], and they are frequently used in pig farms across Indonesia [9,10]. Based on previous studies by Wang et al [11] and Zhang et al [12] various bacterial species have developed resistance to tetracycline through their tet genes.…”
Section: Introductionmentioning
confidence: 99%